Uterine Rupture by Intended Mode of Delivery in the UK: A National Case-Control Study - Fitzpatrick, Kathryn E. (Public Library of Science, 2012)
BACKGROUND: Recent reports of the risk of morbidity due to uterine rupture are thought to have contributed in some countries to a decrease in the number of women attempting a vaginal birth after caesarean section. The aims of this study were to estimate the incidence of true uterine rupture in the UK and to investigate and quantify the associated risk factors and outcomes, on the basis of intended mode of delivery. METHODS AND FINDINGS: A UK national case-control study was undertaken between April 2009 and April 2010. The participants comprised 159 women with uterine rupture and 448 control women with a previous caesarean delivery. The estimated incidence of uterine rupture was 0.2 per 1,000 maternities overall; 2.1 and 0.3 per 1,000 maternities in women with a previous caesarean delivery planning vaginal or elective caesarean delivery, respectively. Amongst women with a previous caesarean delivery, odds of rupture were also increased in women who had ≥ two previous caesarean deliveries (adjusted odds ratio [aOR] 3.02, 95% CI 1.16–7.85) and <12 months since their last caesarean delivery (aOR 3.12, 95% CI 1.62–6.02). A higher risk of rupture with labour induction and oxytocin use was apparent (aOR 3.92, 95% CI 1.00–15.33). Two women with uterine rupture died (case fatality 1.3%, 95% CI 0.2–4.5%). There were 18 perinatal deaths associated with uterine rupture among 145 infants (perinatal mortality 124 per 1,000 total births, 95% CI 75–189). CONCLUSIONS: Although uterine rupture is associated with significant mortality and morbidity, even amongst women with a previous caesarean section planning a vaginal delivery, it is a rare occurrence. For women with a previous caesarean section, risk of uterine rupture increases with number of previous caesarean deliveries, a short interval since the last caesarean section, and labour induction and/or augmentation. These factors should be considered when counselling and managing the labour of women with a previous caesarean section. Please see later in the article for the Editors' Summary